Evaluation of quality indicators and disease damage in childhood-onset systemic lupus erythematosus patients. Issue 2 (February 2017) - Harris, Julia; Maletta, Kristyn; Kuhn, Evelyn; Olson, Judyann
Abstract The aim of this study was to describe compliance with select quality indicators and assess organ-specific dysfunction in a childhood-onset systemic lupus erythematosus population by using a validated damage index and to evaluate associations between compliance with quality indicators and disease damage. A retrospective chart review was performed on patients diagnosed with systemic lupus erythematosus prior to age 18 followed at a single center in the USA from 1999 to 2012 (n  = 75). Data regarding quality indicators and outcome variables, including the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index, were collected. The median disease duration was 3.8 years. The proportion of patients or patient–years in which care complied with the proposed quality measures was 94.4% for hydroxychloroquine use, 84.3% for vitamin D recommendation, 75.8% for influenza vaccination (patient–years), 67.2% for meningococcal vaccination, 49.0% for ophthalmologic examination (patient–years), 31.7% for pneumococcal vaccination, and 28.6% for bone mineral density evaluation. Disease damage was present in 41.3% of patients at last follow-up, with an average damage index score of 0.81. Disease damage at last follow-up was associated with minority race/ethnicity (p  = 0.008), bone mineral density evaluation (p  = 0.035), and vitamin D recommendation (p  = 0.018). Adherence to quality indicators in a childhood-onset systemic lupus erythematosus population is varied, and disease damage is prevalent. This study highlights the importance of quality improvement initiatives aimed at optimizing care delivery to reduce disease damage in pediatric lupus patients.